The Internet as a Data Source for Advancement in Social Sciences - Nikos Askitas; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2015)
This paper advocates the use of Internet data for social sciences with a special focus on human resources issues. It discusses the potentials and challenges of Internet data for social sciences and presents a selection of the relevant literature to establish the wide spectrum of topics, which can be reached. Such data represent a large and increasing part of everyday life, which cannot be measured otherwise. They are timely, perhaps even daily following the factual process, they typically involve large numbers of observations, and they allow for flexible conceptual forms and experimental settings. Internet data can successfully be applied to a very wide range of human resource issues including forecasting (e.g. of unemployment, consumption goods, tourism, festival winners and the like), nowcasting (obtaining relevant information much earlier than through traditional data collection techniques), detecting health issues and well-being (e.g. flu, malaise and ill-being during economic crises), documenting the matching process in various parts of individual life (e.g. jobs, partnership, shopping), and measuring complex processes where traditional data have known deficits (e.g. international migration, collective bargaining agreements in developing countries). Major problems in data analysis are still unsolved and more research on data reliability is needed. Current research is highly original but also exploratory and premature. Our article reviews the current attempts in the literature to incorporate Internet data into the mainstream of scholarly empirical research and guides the reader through this Special Issue. We provide some insights and a brief overview of the current state of research.
Keywords: J00; C80; C81; C83; 330; forecasting; internet data; web data; World Wide Web; human resources and the internet